2009
DOI: 10.1111/j.1526-100x.2008.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrient Manipulations and Grass Removal on Cover, Species Composition, and Invasibility of a Novel Grassland in Colorado

Abstract: Cover and richness of a 5-year revegetation effort were studied with ,respect to small-scale disturbance and nutrient manipulations. The site, originally a relict tallgrass prairie mined for gravel, was replanted to native grasses using a seed mixture of tall-, mixed-, and short-grass species. Following one wet and three relatively dry years, a community emerged, dominated by species common in saline soils not found along the Colorado Front Range. A single species, Alkali sacaton (Sporobolus airoides), compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Those results are in agreement with our measurements of N in soil beneath cheatgrass compared with those beneath the native Pascopryum smithii, suggesting that cheatgrass may have initiated a similar plant-soil N feedback at out site. We also know from previous studies that nutrient limitation can inhibit the ability of introduced annual species to exploit opportunities created by disturbances (Paschke et al 2000, James et al 2008, Cherwin et al 2009). Finally, we found that cheatgrass was one of the only species that responded to fertilizer additions with increased productivity (hence the only species to exhibit N-limitation in our experiment).…”
Section: Discussionmentioning
confidence: 98%
“…Those results are in agreement with our measurements of N in soil beneath cheatgrass compared with those beneath the native Pascopryum smithii, suggesting that cheatgrass may have initiated a similar plant-soil N feedback at out site. We also know from previous studies that nutrient limitation can inhibit the ability of introduced annual species to exploit opportunities created by disturbances (Paschke et al 2000, James et al 2008, Cherwin et al 2009). Finally, we found that cheatgrass was one of the only species that responded to fertilizer additions with increased productivity (hence the only species to exhibit N-limitation in our experiment).…”
Section: Discussionmentioning
confidence: 98%
“…The fact that much of this soil had been stockpiled for an unknown interval meant that what was returned and spread over the surface was very different from what had originally been removed. Measurements of organic matter and organic nitrogen indicated that the soils on the revegetated site were more characteristic of arid shortgrass steppe than of a mesic, bottomland tallgrass prairie (Cherwin et al . in press).…”
Section: Managing Under No‐analog Conditionsmentioning
confidence: 99%
“…Other warm‐season grasses common in mixed‐grass and shortgrass steppe provided another 25% of relative vegetation cover. Particularly remarkable was the fact that planted species constituted over 90% of the vegetation cover and the site appeared largely resistant to invasions by other native and non‐native plants (Cherwin et al . in press).…”
Section: Managing Under No‐analog Conditionsmentioning
confidence: 99%
“…A shift in RAB community composition could affect host fitness, especially if involving mutualist/pathogen abundance. Increasing N availability causes shifts in dominance between plant species (Pennings et al ., ; Suding et al ., ), reductions in plant species diversity (Strengbom et al ., ; Bobbink, ; Suding et al ., ; Clark and Tilman, ) and increased vulnerability of systems to invasion (Bobbink, ; Cherwin et al ., ). Describing root associated microbial response to N is important to understanding plant community response to N enrichment.…”
Section: Introductionmentioning
confidence: 97%